The new normal of remote work: exploring individual and organizational factors affecting work-related outcomes and well-being in academia - Capone, Vincenza; Schettino, Giovanni; Marino, Leda; Camerlingo, Carla; Smith, Alessandro; Depolo, Marco (Frontiers in Psychology, 2024)
Background: Flexible work arrangements have become increasingly popular, driven by the widespread adoption of digital technologies in the workplace because of the pandemic. However, there is a scarcity of studies concerning remote work, especially related to technical-administrative staff (TAS) in academia. Therefore, the current study, adopting the Job Demands-Resources model, aimed to investigate the relationships between remote working self-efficacy, organizational support, techno-complexity, mental well-being, and job performance among TAS during remote working.Method: A total of 373 individuals from TAS of a large Italian university participated in this study by completing a self-report questionnaire.The findings showed positive and significant relationships between remote self-efficacy and job satisfaction as well as between such a perceived efficacy and mental well-being. Perceived support from supervisors acted as a protective factor against techno-complexity. In contrast, perceived support from colleagues emerged as able to promote well-being and job satisfaction. In addition, the latter was positively associated with well-being. Finally, individual job performance was positively affected by job satisfaction and negatively by techno-complexity.This study highlights the need for interventions to support TAS in remote working environments by leveraging employees' self-efficacy as a key factor in reducing stress related to new technologies as well as enhancing well-being, job satisfaction, and, in turn, their performance.